2006
DOI: 10.1007/s00268-005-0165-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Focal Adhesion Kinase in Resectable Pancreatic Cancer

Abstract: Focal adhesion kinase (FAK) is a non-receptor, cytoplasmic protein tyrosine kinase that is involved in the regulation of cellular signaling, migration, apoptosis, and cell cycle progression. Previous reports have shown that FAK is expressed in various kinds of cancer tissues and cancer cell lines; however, no information is available about human pancreatic carcinoma specimens. Tissue such specimens were obtained from 50 patients who underwent pancreatic resection for pancreatic invasive ductal carcinoma at our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 29 publications
3
66
0
Order By: Relevance
“…Increased FAK expression is frequently associated with malignant or metastatic disease and poor patient prognosis (24)(25)(26)(27)(28)(29)(30). FAK expression is increased in various tumors, such as those of the breast, colon, thyroid, head and neck, ovaries, liver, esophagus, and pancreas (24)(25)(26)(27)(28)(29)(30) Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…Increased FAK expression is frequently associated with malignant or metastatic disease and poor patient prognosis (24)(25)(26)(27)(28)(29)(30). FAK expression is increased in various tumors, such as those of the breast, colon, thyroid, head and neck, ovaries, liver, esophagus, and pancreas (24)(25)(26)(27)(28)(29)(30) Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, FAK expression correlates with pancreatic tumor size, but not with tumor grade, metastasis or overall survival. 57 FAK overexpression is not restricted to the invasive phenotype of breast carcinomas but rather appears to be a marker for malignant transformation. 58 These studies suggest that FAK might have different roles in different tumors.…”
Section: Insights Into the Role Of Fak In Tumor Development-dynamic Rmentioning
confidence: 99%
“…FAK overexpression has been shown in many solid carcinomas, including breast, colon, prostate, head and neck, liver, stomach, and ovary. Furthermore, FAK overexpression has been correlated with the invasive potential of a tumor and lymph node metastasis (Cance et al 2000;Canel et al 2006;Furuyama et al 2006;Miyazaki et al 2003;Theocharis et al 2002;Watermann et al 2005); whereas, reduced expression of FAK was found in liver metastases compared with matched primary tumors (Ayaki et al 2001). In agreement with this study, weak expression of FAK in patients with cervical cancer is speciWcally correlated with pelvic lymph node metastasis (Gabriel et al 2006).…”
Section: Introductionmentioning
confidence: 97%